2020
DOI: 10.1149/09901.0265ecst
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of PVD Coatings on Surface of Small Arm

Abstract: This work deals with the possibility of increasing the utility properties of the functional part of the weapon by deposition of PVD coating. These coatings are widely known for their high hardness and abrasion resistance without affecting the anti-corrosion properties. The experimental part evaluates the created duplex coating on the piston of the assault rifle Sa vz. 58. Duplex coating adhesion, surface morphology, and coating thickness was evaluated on opto digital microscope Olympus DSX 500. The impact resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These substitutes include, for example, the deposition of hard, abrasionresistant coatings using PVD (Physical Vapor Deposition) and CVD (Chemical Vapor Deposition) technologies. For example, the application of PVD coatings based on FeinAl (designation of the AlCrN coating) showed that the application of this coating to the gas piston did not lead to its visible wear even after 3,000 shots [17]. However, it should be added that the FeinAl coating was applied to the original hard chrome coating.…”
Section: Introductionmentioning
confidence: 99%
“…These substitutes include, for example, the deposition of hard, abrasionresistant coatings using PVD (Physical Vapor Deposition) and CVD (Chemical Vapor Deposition) technologies. For example, the application of PVD coatings based on FeinAl (designation of the AlCrN coating) showed that the application of this coating to the gas piston did not lead to its visible wear even after 3,000 shots [17]. However, it should be added that the FeinAl coating was applied to the original hard chrome coating.…”
Section: Introductionmentioning
confidence: 99%
“…These substitutes include, for example, the deposition of hard, abrasion-resistant coatings using PVD (Physical Vapor Deposition) and CVD (Chemical Vapor Deposition) technologies. For example, the application of PVD coatings based on FeinAl (designation of the AlCrN coating) showed that the application of this coating to the gas piston did not lead to its visible wear even after 3000 shots [10]. However, it should be noted that the FeinAl coating was applied to the original hard chrome coating.…”
mentioning
confidence: 99%